Grading Anterior Chamber Inflammation with Anterior Segment Optical Coherence Tomography: An Overview. (17th February 2022) - Maring, Morgan; Saraf, Steven S.; Blazes, Marian; Sharma, Sumit; Srivastava, Sunil; Pepple, Kathryn L.; Lee, Cecilia S.
ABSTRACT: The objective grading of anterior chamber inflammation (ACI) has remained a challenge in the field of uveitis. While the grading criteria produced by the Standardization of Uveitis Nomenclature (SUN) International Workshop have been widely adopted, limitations exist including interobserver variability and grading confined to discrete categories rather than a continuous measurement. Since the earliest iterations of optical coherence tomography (OCT), ACI has been assessed using anterior segment OCT and shown to correlate with slit-lamp findings. However, widespread use of this approach has not been adopted. Barriers to standardization include variability in OCT devices across clinical settings, lack of standardization of image acquisition protocols, varying quantification methods, and the difficulty of distinguishing inflammatory cells from other cell types. Modern OCT devices and techniques in artificial intelligence show promise in expanding the clinical applicability of anterior segment OCT for the grading of ACI.